2012
DOI: 10.1007/s00411-012-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative proteomic and microRNA analysis of primary human coronary artery endothelial cells exposed to low-dose gamma radiation

Abstract: High doses of ionising radiation significantly increase the risk of cardiovascular disease (CVD), the vascular endothelium representing one of the main targets. Whether radiation doses lower than 500 mGy induce cardiovascular damage is controversial. The aim of this study was to investigate radiation-induced expression changes on protein and microRNA (miRNA) level in primary human coronary artery endothelial cells after a single 200 mGy radiation dose (Co-60). Using a multiplex gel-based proteomics technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…This implies that low doses of ionizing radiation likely have stimulating effects on the secretome, which is in agreement with proteomic studies of endothelial cell exposure to low dose gamma radiation (<50 cGy) [35], [36]…”
Section: Resultssupporting
confidence: 84%
“…This implies that low doses of ionizing radiation likely have stimulating effects on the secretome, which is in agreement with proteomic studies of endothelial cell exposure to low dose gamma radiation (<50 cGy) [35], [36]…”
Section: Resultssupporting
confidence: 84%
“…Mechanistically, circulating EGFR protein mobilizes EPCs by activating matrix metalloproteinase-9 (MMP-9), which cleaves membrane-bound cKit ligand to release soluble cKit ligand (also known as stem cell factor) [29,30]. This then stimulates cKit + stem cells, including EPCs, to migrate from a quiescent bone marrow niche to the vascular zone, thereby translocating the cells into a proliferative state [17]. Thus, anti-EGFR miRNAs identified in this study may contribute only in part of the reduced EPC number and activity in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Strain specific differences in low-dose radiation effects on atherosclerosis progression after exposure at early and late stage disease in knockouts (ApoE-/-). alterations, suggesting that the involvement of these small noncoding RNAs in the cellular response to ionizing radiation exposure [62]. Interestingly, recent work has shown that microRNAs can modulate the regulation of radiation-induced DNA damage and premature senescence [63].…”
Section: Biological Mechanismsmentioning
confidence: 98%